True Relations : Reading, Literature, and Evidence in Seventeenth-Century England - Dolan, Frances E. (Frances Elizabeth), 1960- (Book collections on Project MUSE., 2013)
Examining seventeenth-century crises of evidence and genres of evidence on which both literary critics and historians depend, this book explores the notion that we apprehend truth through other people's relations of it and that those relations, and our own relation to them, are a function of social relationships in conflict.